The Effect of Labeling and Numbering of Response Scales on the Likelihood of Response Bias. Issue 1 (August 2014) - Moors, Guy; Kieruj, Natalia D.; Vermunt, Jeroen K.
Extreme response style (ERS) and acquiescence response style (ARS) are among the most encountered problems in attitudinal research. The authors investigate whether the response bias caused by these response styles varies with following three aspects of question format: full versus end labeling, numbering answer categories, and bipolar versus agreement response scales. A questionnaire was distributed to a random sample of 5, 351 respondents from the Longitudinal Internet Studies for the Social Sciences household panel, of which a subsample was assigned to one of five conditions. The authors apply a latent class factor model that allows for diagnosing and correcting for ERS and ARS simultaneously. The results show clearly that both response styles are present in the data set, but ARS is less pronounced than ERS. With regard to format effects, the authors find that end labeling evokes more ERS than full labeling and that bipolar scales evoke more ERS than agreement style scales. With full labeling, ERS opposes opting for middle response categories, whereas end labeling distinguishes ERS from all other response categories. ARS did not significantly differ depending on test conditions.